Regional Policy of the European Union Versus Sustainable Development - Kazimierz Górka; Paulina Szyja (Barometr Regionalny, 2012)
The authors begin with the statement that Western Europe, as in the USA, commenced activities aimed at overcoming financial and economic crisis with the bailing out of financial and banking institutions while neglecting stimulation of real economic policy. Nonetheless, the strategic plan of the European Union called ‘Europe 2020’ points out that ensuring lasting economic growth and social development are prerequisite. In the subsequent parts of the article the authors present an evaluation of the importance of regional policy for economic stimulation of the EU. To this end the authors analyze the EU budgetary expenditures on cohesion policy and the impact those expenditures make on sustainable development; they also present some methods of transforming the European economy into a low emission (green) model.